Conservation Laws of Discrete Korteweg-de Vries Equation - Rasin, O.G.; Hydon, P.E. (Symmetry, Integrability and Geometry: Methods and Applications, 2005)
All three-point and five-point conservation laws for the discrete Korteweg-de Vries equations are found. These conservation laws satisfy a functional equation, which we solve by reducing it to a system of partial differential equations. Our method uses computer algebra intensively, because the determining functional equation is quite complicated.